Research Trends of Local Wisdom-Based Media to Improve Science Literacy - Eka Muliati; Dedy Suhendra; Yunita Arian Sani A (Current Educational Review, 2025)
Scientific literacy is the ability of individuals to understand and use scientific knowledge in asking questions, seeking information, explaining natural phenomena, and making decisions based on evidence. This literacy also includes awareness of the impact of science and technology on the environment, culture, and daily life, as well as encouraging active engagement with science-related issues. This study aims to identify and analyze research trends related to local wisdom-based media in improving scientific literacy. The method used is descriptive and analytical, with data obtained from documents indexed in Google Scholar and Dimensions.ai within the period of 2016–2025, using tools such as Publish or Perish and Dimensions.ai. The research procedure follows the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. The analyzed data includes types of publications, sources of publications, and research titles. The analysis was carried out bibliometrically using VOSviewer software. The results show that the research trend on local wisdom-based media has shown a fluctuating pattern. From 2016 to 2019, the number of publications gradually increased. In 2020, there was a significant spike, followed by steady growth until 2024. The decline in 2025 is presumed to be due to the current year's data not being fully accumulated. Most documents are in the form of articles, books, proceedings, and monographs. Frequently appearing keywords in this research are: Scientific Literacy, Learning Media, Local Wisdom, Contextual Learning, and Science Education